User guide to the toolbox for working with root, tuber and banana seed systems. RTB User guide - Andrade-Piedra, J.L.; Almekinders, Conny J.M.; McEwan, M.; Kilwinger, Fleur B.M.; Mayanja, S.; Mulugo, L.; Delaquis, Erik; Garrett, K.A.; Omondi, Bonaventure Aman Oduor; Rajendran, S.; Kumar, P. Lava; Thiele, Graham (International Potato Center, 2020)
This user guide to the Toolbox for working with root, tuber and banana seed systems introduces tools to diagnose, evaluate, and improve seed systems of banana, cassava, potato, sweetpotato, and yam. As a whole, these crops are called roots, tubers and bananas, and they are crucial for food security and income generation, especially in developing countries. All of these crops are reproduced vegetatively, from roots, tubers, stems, suckers or vines. This bulky planting material is expensive to transport. Vegetative seed is perishable and (except for potatoes, yams and a few other exceptions) must be planted as fresh as possible, and it is more likely to carry pests and diseases than true seed. Besides these unique challenges, improved seed systems of root, tuber and banana crops give farmers the opportunity to boost their livelihoods by accessing better quality planting material from landraces or improved varieties that are high yielding, resistant to stresses, more nutritious or more responsive to consumer demand.